2008
DOI: 10.1002/adfm.200800354
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Nanocomposite Coatings with Tunable Cell Adhesion and Bactericidity

Abstract: TiO2‐Ag nanocomposites are known for their bactericidal effect during exposure to appropriate UV radiation. While involving hazardous radiation, and limited to accessible areas, the bactericidity of these coatings is not persistent in the absence of UV light, which impedes their commercial application. Herein it is shown that TiO2‐Ag nanocomposites can be made highly bactericidal without the need of irradiation. Beyond this, bactericidity can even be mitigated in the presence of pre‐irradiated coatings. Biocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 46 publications
3
44
0
Order By: Relevance
“…[26] Therefore, we concluded that deformation in the a phase is dominant in near-a Ti alloys with a small volume fraction of b phase, even though the activation energy in a-Ti is affected by solute diffusion. [36] The activation energies obtained in this study are greater than that for self-diffusion in a-Ti and are similar to the values reported for conventional alloys such as Ti-6242S and IMI 834, [27,32,33] even though the effects of Si solid solution and silicide precipitation were not factors in this study. Figure 4 shows the mass gain per unit area of the alloys oxidized in air for 340 hours at 973 K (700°C) (a) and for 240 hours at 1023 K (750°C) (b).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…[26] Therefore, we concluded that deformation in the a phase is dominant in near-a Ti alloys with a small volume fraction of b phase, even though the activation energy in a-Ti is affected by solute diffusion. [36] The activation energies obtained in this study are greater than that for self-diffusion in a-Ti and are similar to the values reported for conventional alloys such as Ti-6242S and IMI 834, [27,32,33] even though the effects of Si solid solution and silicide precipitation were not factors in this study. Figure 4 shows the mass gain per unit area of the alloys oxidized in air for 340 hours at 973 K (700°C) (a) and for 240 hours at 1023 K (750°C) (b).…”
Section: Resultssupporting
confidence: 86%
“…[27][28][29][30][31][32][33][34][35] The superior creep strength with the small volume fraction of equiaxed a phase in the present study is attributed to the concomitant effect of the following factors: (1) a larger colony size and prior b-grain size with a large volume of lamellar structure, which determines the dislocation-gliding distance; (2) possibly less grain-boundary sliding [34,35] ; and (3) an increase in the strength of the lamellar matrix in the bimodal structure as a consequence of alloy-element partitioning. [29] In the case of higher activation energies, the rate-controlling process at higher temperatures was assumed to be diffusion controlled because the activation energy for the high-temperature creep was similar to that of self-diffusion in a-Ti (e.g., 242 kJ/mol).…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8] On the other hand, silver (Ag) nanoparticles have long been known to liberate silver ions in liquids that show a broad spectrum over the antimicrobial activities. 9,10 Immobilization of Ag nanoparticles on TiO 2 to form hybrid composite particles with tailored structure and surface functionality has been demonstrated to show improved photocatalytic activity, 3,[11][12][13] as well as bactericidal activity [14][15][16] without the need of UV irradiation. * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…1) In these activities, titanium based alloys are developed as structural materials for engine of aircraft, aerospace components, hydrogen storage materials and shape memory alloys due to their low density, high strength and modulus, corrosion resistance and other eminent properties. In spite of these advantages, applications of Ti alloys are still limited by high temperature.…”
Section: Introductionmentioning
confidence: 99%